Well-being in the Digital Age : Unravelling the Influence of Team Mindfulness and Psychological Safety in Global Virtual Teams - Islam, Rakibul (My University, 2024)
This study investigates the intricate dynamics between team mindfulness, psychological safety, and well-being within the context of global virtual teams. Drawing upon a sample of 466 students from diverse nationalities participating in an international business strategy course, data was collected through online surveys conducted over four years. The study employs quantitative analysis to explore the relationships between team mindfulness, psychological safety, and individual well-being. Findings reveal a direct positive correlation between team mindfulness and individual well-being, with specific components like nonjudgmental processing playing a significant role. Additionally, team psychological safety emerges as a crucial factor shaping individual well-being, emphasizing the importance of creating a supportive environment where team members feel safe to express themselves. The study uncovers a symbiotic relationship between team mindfulness and psychological safety, although psychological safety was not found to mediate the relationship between team mindfulness and well-being. Theoretical contributions of this study include a shift from individual-level to team-level constructs in understanding well-being within virtual teams, opening avenues for future research. From a practical standpoint, the study underscores the importance of fostering team mindfulness and psychological safety to enhance well-being in global virtual teams, providing valuable insights for scholars and practitioners striving to optimize team dynamics and member well-being in virtual team settings.
Keywords: Global Virtual Team, Well-being, Team Mindfulness, Psychological Safety, Conservation of Resources Theory (COR)